Impact of Social Interaction and Knowledge Management on Job Satisfaction Mediated by Organizational Citizenship Behavior - Rofikul Amin; Roby Nur Akbar; Adi Suprayitno; Agus Haryono; Isman Isman; Mohamad Nur Singgih (Trescode Green Organization, 2025)
This study aims to analyze the influence of social interaction and knowledge management on job satisfaction, with Organizational Citizenship Behavior (OCB) as a mediating variable among employees of BCA Bank in East Java in 2024. The research employs a quantitative approach, using primary data collected through an online questionnaire from 99 respondents. Data analysis was conducted using Partial Least Squares (PLS) to examine the relationships between variables. The findings reveal that social interaction has a significant direct effect on job satisfaction, underscoring the importance of communication and collaboration among employees in fostering a positive work environment. Conversely, knowledge management does not exhibit a significant impact on job satisfaction, either directly or indirectly through OCB, indicating that the knowledge management strategies currently implemented are suboptimal. Furthermore, OCB fails to mediate the relationship between social interaction and knowledge management with job satisfaction. The conclusion of this study highlights the importance of adopting a more strategic approach focused on strengthening social interactions and optimizing knowledge management to enhance job satisfaction. This research offers practical implications for human resource management to cultivate a more collaborative work culture and support OCB behavior, ultimately improving employee productivity and overall well-being.